2018
DOI: 10.2174/1567205015666180404155358
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Patterns in Signs and Symptoms Preceding the Clinical Diagnosis of Alzheimer’s Disease: Retrospective Medical Record Review Study and a Nested Case-control Design

Abstract: Limited sample size that will not allow for generalization of less frequent observations due to their low prevalence in case notes. Randomisation was not achieved; however, the best available nonrandomisation which is consecutive sampling was used. Patterns identified were in LOAD, the baseline could vary with other geographical areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Conversely, a Finnish register-based study with up to 33 years of follow-up found no association between anxiety and AD with neither 5 nor 10 years interval between diagnoses (Tapiainen et al, 2017). Another study from the UK with up to 27 years follow-up was not able to find an association between anxiety and AD (Bature et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Conversely, a Finnish register-based study with up to 33 years of follow-up found no association between anxiety and AD with neither 5 nor 10 years interval between diagnoses (Tapiainen et al, 2017). Another study from the UK with up to 27 years follow-up was not able to find an association between anxiety and AD (Bature et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…One study looking at both British and French routine data found evidence of association between malaise and fatigue with future AD diagnosis within 2 (OR UK = 1.36; 95% CI: 1.17 to 1.58 | OR Fr = 1.78; 95% CI: 1.59 to 2.0) and 2-10 years (OR UK = 1.23; 95% CI: 1.08 to 1.39 | OR Fr = 1.59; 95% CI: 1.36 to 1.86). They also found Syncope and collapse to be more common prior to AD diagnosis within 2 years (OR UK = 1.95; 95% CI: 1.53 to 2.48 | OR Fr = 2.49; 95% CI: 1.68 to 3.69) and 2-10 years (OR UK = 1.23; 95% CI: 1.01 to 1.5 | OR Fr = 1.57; 95% CI: 1.06 to 2.34) (Bature et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hippocampus is an important part of the brain due to its anatomical structure and physiological functions, especially in the area related to learning and memory under normal conditions and dementia in Alzheimer's disease and brain injury after ischemia [1][2][3][4][5][6][7]. The hippocampus plays an important role in the consolidation of information from short-term memory to long-term memory and spatial orientation, and this important transmission is disturbed inter alia in Alzheimer's disease [3,4]. In addition, various areas of pyramidal neurons in the hippocampus also show a rather specialized response to pathological factors, as exemplified by similar neurodegenerative changes in Alzheimer's disease and cerebral ischemia [5,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%